An Analysis of Students’ Errors in Writing Analytical Exposition Text by Using Surface Strategy Taxonomy - Ilham, Galih Fahrizal; Rohimajaya, Nur Azmi; Novari, Ari Fajria; Hamer, Welliam (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
Writing as a complex process that students must go through in order to communicate what is on their minds and then represent it in the form of text when studying English. The purpose of this research article was to analyze students' errors in writing analytical exposition texts for Indonesian senior high school students. The article employed a qualitative research design with descriptive research characteristics. Methods of data collection included observation, interviews, and documentation. Observation, interviews, and documentation were used as instruments. The information was gathered during three meetings. The interview with the teacher took place before the observation, and the interview with the students took place after the analysis of the student's worksheets. From the findings of the article, it can be informed that the errors made by students fall into the categories of omission error, addition error, misformation error, and misordering error. There were 67 total errors, including 54 omission errors with an omission error percentage of 80.59 percent, seven addition errors with a percentage of 10,44 percent, six misordering errors with an omission error percentage of 8,95 percent, and no error in misformation. The most common error made by students was omission error, followed by addition, misordering, and misformation errors. This was due to students' lack of vocabulary mastery, as well as their incorrect use of grammar and structure. This article suggests that teachers should be more innovative in their use of various teaching strategies, as well as should be more interactive and communicative with their students. The students, should be serious and pay attention to the teacher's explanation during the teaching and learning process, they should explore more vocabulary, do many exercises, and reduce their chances of making errors.